Life history traits of Sirex noctilio F. (Hymenoptera: Siricidae) can explain outbreaks independently of environmental factors - Aparicio, Juan Pablo (2013)
The woodwasp Sirex noctilio is a major pest of pine plantations worldwide. Economically significant damage is however limited to outbreak populations. To understand what determines outbreaks dynamics in this species, we developed an individual based model for a wasp population developing within a pine plantation. We show that outbreaks may be the result of the insect's life history. Specifically we show that limited dispersal may not only increase population persistence but also create the conditions for eruptive dynamics. When the probability of long distance dispersal is greater than zero, but relatively small (PLDD= 0.1) large outbreaks are the norm, with all of the suitable trees dead at the end of the simulation. For PLDD= 0 (only local dispersal allowed) outbreaks are smaller in size, and in some cases not well defined and spread over longer periods. For PLDD= 1 (only long distance dispersal allowed), the frequency of local population extinction (without outbreaks) increases significantly. Aggregated attacks may induce physiological changes in the trees which could allow other wasps to detect them. These changes may in turn trigger an outbreak. In contrast, healthy, vigorous trees are not suitable for wasp oviposition. In our model the density of suitable trees (healthy trees but yet suitable for oviposition) are a key factor determining population persistence before outbreaks. From an applied perspective, our results emphasize the importance of adequate plantation management in preventing woodwasp infestation.